Sequence characterization of coding regions of the myostatin gene (GDF8) from Brazilian Murrah buffaloes (Bubalus bubalis) and comparison with the Bos taurus sequence - Mota, Lígia S.L.S. [UNESP]; Curi, Rogerio Abdallah [UNESP]; Palmieri, Darío A. [UNESP]; Borges, Alexandre Secorun [UNESP]; Lopes, Catalina R. [UNESP]; Barbosa, José D.; Gimenes, Marcos A. [UNESP] (Sociedade Brasileira de Genética, 2006)
Within about 30 years the Brazilian buffalo (Bubalus bubalis) herd will reach approximately 50 million head as a result of the great adaptive capacity of these animals to tropical climates, together with the good productive and reproductive potential which make these animals an important animal protein source for poor and developing countries. The myostatin gene (GDF8) is important in the physiology of stock animals because its product produces a direct effect on muscle development and consequently also on meat production. The myostatin sequence is known in several mammalian species and shows a high degree of amino acid sequence conservation, although the presence of non-silent and silent changes in the coding sequences and several alterations in the introns and untranslated regions have been identified. The objective of our work was to characterize the myostatin coding regions of B. bubalis (Murrah breed) and to compare them with the Bos taurus regions looking for variations in nucleotide and protein sequences. In this way, we were able to identify 12 variations at DNA level and five alterations on the presumed myostatin protein sequence as compared to non double-muscled bovine sequences.
Keywords: buffalo; GDF8; myostatin